2010
DOI: 10.1016/j.ygcen.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gestational androgen levels in female marmosets (Callithrix geoffroyi) vary across trimesters but do not vary with the sex ratio of litters

Abstract: Maternal hormones can dramatically modify offspring phenotypes via organizational actions on morphological and behavioral development. In placental mammals, there is the possibility that some portion of hormones in maternal circulation may be derived from fetal origin. We tested the possibility that maternal androgens in pregnant female marmosets reflected, in part, contributions from male fetuses by comparing levels of urinary androgens across pregnancy in females carrying varying numbers of male offspring. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…The placenta is a steroid-rich tissue, and androgens and their metabolic precursors can be produced from this source [14]. Testicular production of androgens by male fetuses can cross the fetal-placental barrier and enter general circulation in pregnant females, although this does not inevitably occur in all species (literature reviewed in French et al [31]). Finally, androgens of adrenal origin, although typically secreted at substantially lower levels than those of gonadal origin, can nonetheless contribute to overall circulating androgen levels [32].…”
Section: Lemurs (Lemur Spp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The placenta is a steroid-rich tissue, and androgens and their metabolic precursors can be produced from this source [14]. Testicular production of androgens by male fetuses can cross the fetal-placental barrier and enter general circulation in pregnant females, although this does not inevitably occur in all species (literature reviewed in French et al [31]). Finally, androgens of adrenal origin, although typically secreted at substantially lower levels than those of gonadal origin, can nonetheless contribute to overall circulating androgen levels [32].…”
Section: Lemurs (Lemur Spp)mentioning
confidence: 99%
“…The impact of having a male versus female co-twin on female behavioural development has not been systematically examined to date. However, it is clear that marmoset fetuses are exposed to high and varying concentrations of maternally derived androgens in utero [31], with significant effects on later development. We demonstrated that differences in gestational exposure of fetuses to androgens influenced both morphological and behavioural development.…”
Section: (A) Prenatal Androgen Exposurementioning
confidence: 99%
“…The mechanisms underlying androgen production during gestation in Assamese macaques are not known, however, elevated androgens during pregnancy in primates are likely to be under regulation of CG, as in several species increasing androgen concentrations coincide with increasing CG concentrations (e.g., Castracane and Goldzieher, 1983;Rao and Kotagi, 1983;French et al, 2010). Also, the sources of origin of the androgens excreted by our pregnant study females remain to be established but it is likely that they are derived from multiple sources, including the ovary, corpus luteum, placenta, and presumably adrenal (e.g., Hodges et al, 1984;Castracane et al, 1998).…”
Section: Fecal Androgen Patterns Throughout Pregnancymentioning
confidence: 99%
“…Hence, in a number of mammal species (including primates) females carrying male fetuses show higher androgen concentrations at certain stages of gestation compared with females carrying female fetuses (e.g., humans: Meulenberg and Hofman, 1991;elephants: Duer et al, 2002;baboons: Altmann et al, 2004;lemurs: Drea, 2011); however, other studies did not find this relationship (e.g., Glass and Klein, 1981;Steler et al, 2002;Troisi et al, 2003;French et al, 2010). Thus, maternal androgens can be derived solely from maternal sources or reflect both maternal plus fetal contributions.…”
mentioning
confidence: 99%
See 1 more Smart Citation